Learning Environment and Learning Outcome: Evidence from Korean Subject–Predicate Honorific Agreement - Shin, Gyu-Ho; Jung, Boo Kyung; Yang, Minseok (Languages (Basel), 2025)
This study examines the relationship between learning environments and learning outcomes in acquiring Korean as a language target. We compare two learner groups residing in the United States: English-speaking learners of Korean in foreign language contexts versus Korean heritage speakers. Both groups share English as their dominant language and receive similar tertiary-level instruction, yet differ in their language-learning profiles. We measure two groups’ comprehension behaviour involving Korean subject−predicate honorific agreement, focusing on two conditions manifesting a mismatch between the honorifiable status of a subject and the realisation of the honorific suffix in a predicate. Results from the acceptability judgement task revealed that (1) both learner groups rated the ungrammatical condition as more acceptable than native speakers did, (2) Korean heritage speakers rated the ungrammatical condition significantly lower than English-speaking learners, and (3) overall proficiency in Korean modulated learners’ evaluations of the ungrammatical condition in opposite directions between the groups. No between-group difference was found in the infelicitous-yet-grammatical condition. Results from reaction time measurement further showed that Korean heritage speakers responded considerably faster than English-speaking learners of Korean. These results underscore the critical role of broad usage experience—whether through home language exposure for heritage language speakers or formal instruction for foreign language learners—in shaping non-dominant language activities.